Characterization of N-demethyllincosamide methyltransferases LmbJ and CcbJ - Najmanová, Lucie; Kutejová, Eva; Kadlec, Jan; Polan, Marek; Olšovská, Jana; Benada, Oldřich; Novotná, Jitka; Kameník, Zdeněk; Halada, Petr; Bauer, Jacob; Janata, Jiří (Chembiochem, 2013)
Chemical diversity: Two SAM-dependent N-methyltransferases-LmbJ from the biosynthesis of the antibiotic lincomycin and CcbJ from celesticetin biosynthesis-have been characterized and compared. Both tested enzymes form multimers and are able to utilize N-demethyllincomycin, the natural substrate of LmbJ, with comparable efficiency.
Keywords: molekulární konformace; Molecular Conformation; Substrate Specificity; Methyltransferases; lincomycin; linkosamidy; antibakteriální látky; natural products; antibiotics; biokatalýza; N-methyltransferases; Lincosamides; Anti-Bacterial Agents; substrátová specifita; Biocatalysis; Lincomycin; linkomycin; methyltransferasy; Streptomyces